Clinical profile and short-term outcomes of RT-PCR- positive patients with COVID-19: a cross-sectional study in a tertiary care hospital in Dhaka, Bangladesh - Hasan, Md Zabir; Biswas, Nirmol Kumar; Aziz, Ahmad Monjurul; Chowdhury, Juli; Haider, Shams Shabab; Sarker, Malabika (BMJ open, 2021)
Objective The COVID-19 pandemic is still raging worldwide. While there is significant published evidence on the attributes of patients with COVID-19 from lower-income and middle-income countries, there is a dearth of original research published from Bangladesh, a low-income country in Southeast Asia. Based on a case series from a tertiary healthcare centre, this observational study has explored the epidemiology, clinical profile of patients with COVID-19 and short-term outcomes in Dhaka, Bangladesh. - Design and setting A total of 422 COVID-19-confirmed patients (via reverse transcription-PCR test) were enrolled in this study (male=271, female=150, 1 unreported). We have compiled medical records of the patients and descriptively reported their demographic, socioeconomic and clinical features, treatment history, health outcomes, and postdischarge complications. - Result Patients were predominantly male (64%), between 35 and 49 years (28%), with at least one comorbidity (52%), and had COVID-19 symptoms for 1 week before hospitalisation (66%). A significantly higher proportion (p<0.05) of male patients had diabetes, hypertension and ischaemic heart disease, while female patients had asthma (p<0.05). The most common symptoms were fever (80%), cough (60%), dyspnoea (41%) and sore throat (21%). The majority of the patients received antibiotics (77%) and anticoagulant therapy (56%) and stayed in the hospital for an average of 12 days. Over 90% of patients were successfully weaned, while 3% died from COVID-19, and 41% reported complications after discharge. - Conclusion The diversity of clinical and epidemiological characteristics and health outcomes of patients with COVID-19 across age groups and gender is noteworthy. Our result will inform the clinicians and epidemiologists of Bangladesh of their COVID-19 mitigation effort.